The anterior sylvian point as a reliable landmark for the anterior temporal lobectomy in mesial temporal lobe epilepsy: technical note, case series, and cadaveric dissection - Fava, Arianna; Lisi, Serena Vittoria; Mauro, Luigi; Morace, Roberta; Ciavarro, Marco; Gorgoglione, Nicola; Petrella, Giandomenico; Quarato, Pier Paolo; Di Gennaro, Giancarlo; di Russo, Paolo; Esposito, Vincenzo (Frontiers in Medicine, 2024)
Introduction: Mesial Temporal Lobe Epilepsy (MTLE) stands as the most prevalent form of focal epilepsy in surgical series, particularly among adults. Over the decades different surgical strategies have been developed to address drug-resistant epilepsy while safeguarding neurological and cognitive functions. Among these, Anterior Temporal Lobectomy (ATL), involving the removal of the temporal pole and mesial temporal structures, has emerged as a widely employed technique. Numerous modifications have been proposed to mitigate the risks associated with aphasia, cognitive issues, and visual field defects.Methods: Our approach is elucidated through intraoperative and cadaveric dissections, complemented by neuroradiological and cadaveric measurements of key anatomical landmarks. A retrospective analysis of patients with drugresistant MTLE treated using our ATL technique at IRCCS Neuromed (Pozzilli) is presented.Results: 385 patients were treated with our ATL subpial technique anatomically focused on the anterior sylvian point (ASyP). Mean FU was 9.9 ± 5.4 years (range 1-24). Eighty-four % patients were free of seizures at last follow up, with no permanent neurological deficits. Transient defects were: aphasia in 3% of patients, visual field defects in 2%, hemiparesis in 2%, and cognitive/memory impairments in 0.8%. In cadaveric dissections, the ASyP was found at a mean distance from the temporal pole of 3.4±0.2 cm (range 3-3.8) at right side, and 3.5±0.2 cm (3.2-3.9) at the left side. In neuroimaging, the ASyP resulted anterior to the temporal horn tip in all cases at a mean distance of 3.2 ±0.3 mm (range 2.7-3.6) at right side, and 3.5±0.4 mm (range 2.8-3.8) at the left side.Discussion: To the best of our knowledge, this work firstly introduce the ASyP as reliable and reproducible cortical landmark to perform the ATL in order to overcome the patients'variabilities, the risk of Meyer's loop injury, and the bias of intraoperative measurements. Our findings demonstrate that ASyP can be a safe cortical landmark useful in MTLE surgery because constantly present and anterior to risky temporal regions as temporal horn and language networks.